1978
DOI: 10.1210/endo-102-2-540
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Secretion in the Rat in Response to Chorionic Gonadotrophin: Alterations with Age

Abstract: It has been reported by others that both prevailing blood concentrations of testosterone and Leydig cell response to gonadotrophin (up to 1 h after injection) are reduced in the aged male rat. Although resting levels of plasma testosterone in our aged (24-26 months old) Sprague-Dawley rat are also depressed compared with young (3-4 months) or mature (12 months) animals of the same strain, subcutaneous injection with human chorionic gonadotrophin for 3 days restores secretory function, producing testosterone le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Similar to the age-related loss of basal blood testosterone concentrations, the acute response (<1-4h) of the rat testis to gonadotropin (hCG) stimulation in vivo is also impaired in older rats [171][172][173]. Moreover, chronic hCG treatment (3-7 days) was shown to restore plasma testosterone levels of older rats to levels comparable to those of similarly stimulated young mature Wistar [173] or LongEvans [174] rats. In contrast, treating rats for up to three weeks with hCG, Lin et al, [175] were unable to restore testosterone levels in 24-month old Sprague-Dawley rats to values seen in identically treated young mature rats.…”
Section: Experimental Animalsmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar to the age-related loss of basal blood testosterone concentrations, the acute response (<1-4h) of the rat testis to gonadotropin (hCG) stimulation in vivo is also impaired in older rats [171][172][173]. Moreover, chronic hCG treatment (3-7 days) was shown to restore plasma testosterone levels of older rats to levels comparable to those of similarly stimulated young mature Wistar [173] or LongEvans [174] rats. In contrast, treating rats for up to three weeks with hCG, Lin et al, [175] were unable to restore testosterone levels in 24-month old Sprague-Dawley rats to values seen in identically treated young mature rats.…”
Section: Experimental Animalsmentioning
confidence: 92%
“…The rat is the most popular laboratory animal to examine the effects of aging on testicular androgen synthesis and secretion. A number of studies carried out during the past few decades have led to a clear demonstration that aging leads to significant reduction in blood testosterone levels in several rat strains [157][158][159][160][161][162][163][164][165][166][167][168][169].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Gorecki (2003) reported that different sires with different testosterone levels could have different gender ratios in their progeny. In this study, older sires had more female progeny, which could be due to lower testosterone levels compared to younger sires (Harman et al, 1978).…”
Section: Discussionmentioning
confidence: 61%
“…This observation is also consistent with the earlier reports cited above (13 -17), many of which are from studies on males. Since androgens as well as estrogens have been shown to potentiate wound healing (6-9), and reductions in both androgen levels and androgen sensitivity have been found in aged rats (20)(21)(22)(23) there may also be an endocrine contribution to reduced wound healing in old males. It is not possible to determine from the present data whether estrogen sensitivity is reduced in the senescent group.…”
Section: Granulation Tissue Polys In Crust Polys In Woundmentioning
confidence: 99%